2015
DOI: 10.7324/japs.2015.50206
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, molecular docking and QSAR studies of 2, 4-disubstituted thiazoles as antimicrobial agents

Abstract: In present study a series of 2,4-disubstituted thiazole derivatives was synthesized and evaluated for their in vitro antibacterial and antifungal activities against B. subtilis, E. coli, S. aureus, C. albicans and A. niger by tube dilution method. The analysis of antimicrobial activity results indicated that the presence of NO2 and OCH3 groups at para position of phenyl group improved the antimicrobial activity significantly. Molecular docking studies also supported in vitro activity results and showed that NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…The activity data for all compounds were taken from different scientific groups in terms of inhibitory activity (MIC μg/ml) (Jasmine et al, 2012; Shruthi et al, 2012; Jayanna et al, 2013; Hareesh et al, 2015; Preeti et al, 2015; Talavara et al, 2016). Fifty compounds out of hundred, were selected as a training set based following criteria that will produce a good quantitative structural activity relationship (QSAR) model.…”
Section: Methodsmentioning
confidence: 99%
“…The activity data for all compounds were taken from different scientific groups in terms of inhibitory activity (MIC μg/ml) (Jasmine et al, 2012; Shruthi et al, 2012; Jayanna et al, 2013; Hareesh et al, 2015; Preeti et al, 2015; Talavara et al, 2016). Fifty compounds out of hundred, were selected as a training set based following criteria that will produce a good quantitative structural activity relationship (QSAR) model.…”
Section: Methodsmentioning
confidence: 99%
“…The highest activity showed by T3 might be due to the presence of electron donating group which is methoxy (OCH 3 ), which enhance its interaction towards the tested bacteria. Incorporation of methoxy group in the thiazole compound has boosted the antimicrobial activity in terms of increase in lipophilicity behavior that easily penetrated into the membrane of bacterial strains [29]. Besides, methoxy group also provides electron donating behaviour which enhanced the overall antibacterial activity of the synthesized compound [30].…”
Section: Antibacterial Activitiesmentioning
confidence: 99%
“…Narang and coworkers reported 2,4‐disubstituted thiazole derivatives from 2‐amino‐4‐phenylthiazole and screened them against B. subtilis , E. coli , S. aureus , A. niger and C. albicans for antimicrobial effectiveness in reference to Ciprofloxacin and Fluconazole. Complementing with molecular docking study outcomes, enhanced activity was observed by methoxy group (MIC 4.49‐4.60 μm/mL) inclusion at para position of phenyl ring ( 55 ).…”
Section: Introductionmentioning
confidence: 99%